Self-Efficacy dan Mindfulness sebagai Prediktor Keberhasilan Tugas Akhir Mahasiswa - Ariyani, Nili; Surawan, Surawan (Lembaga Yasin AlSys, 2025)
Final-year students often face high academic pressure during the thesis writing process, which requires not only cognitive abilities but also strong psychological resilience. Issues such as low self-confidence and difficulty maintaining focus are major obstacles to completing the final project optimally. This study aims to analyze the extent to which self-efficacy and mindfulness influence students’ success in completing their final projects. A correlational quantitative approach was employed using a survey method involving 43 final-year students at IAIN Palangka Raya. Data were collected through an online questionnaire consisting of 23 Likert-scale statements covering three main indicators: self-efficacy, mindfulness, and final project completion success. Data analysis was conducted using multiple linear regression and Pearson correlation tests. The findings reveal that the combination of self-efficacy and mindfulness significantly contributes 48.7% to the success of final project completion, with self-efficacy emerging as the dominant predictor. These results indicate that students with high self-confidence and full awareness in managing stress and time tend to complete their final projects more effectively and efficiently. In conclusion, strengthening psychological aspects, particularly self-efficacy and mindfulness plays a strategic role in supporting students’ academic success. The study’s implications highlight the importance of developing mental health programs and integrated counseling services in higher education institutions, while also encouraging academic advisors to consider students’ psychological factors in order to provide more comprehensive and solution-oriented guidance.